MA Defence: â€œCreativity Within Constraints: Encoding, Production, and Representation in Battlestar Galacticaâ€ by Philippa Adams - Phan, Vu Thuy Anh (Stream: Interdisciplinary Journal of Communication, 2015)
Our dear colleague, Philippa Adams, will defend her MA Thesis on Friday, December 10th, 2015 at Harbour Centre, Room 1520 (2:00 pm - 4:00 pm). Here is the abstract of her thesis “Creativity Within Constraints”.